Metal-supported carbon fiber catalyst prepared from textile waste, preparation method and application thereof

By using textile waste to prepare metal-supported carbon fiber catalysts, the problems of poor catalyst stability and low catalytic efficiency in the prior art are solved, efficient degradation of difficult-to-degrade organic pollutants in wastewater is achieved, and resource utilization and application efficiency of carbon fiber materials are improved.

CN118491523BActive Publication Date: 2025-03-04TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410663578.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-27
Publication Date
2025-03-04
Estimated Expiration
2044-05-27

AI Technical Summary

Technical Problem

The prior art has problems of poor catalyst stability and low catalytic efficiency in degrading difficult-to-degrade organic pollutants, and the resource shortage and high cost of carbon fiber materials limit their application.

Method used

By using textile waste to prepare metal-supported carbon fiber catalysts, a one-step roasting method is used to synthesize carbon fiber materials with orderly structures and controllable performance, and a poor/rich electron center is built on the surface of the catalyst to improve the metal dispersion and activity of the catalyst surface.

Benefits of technology

It has achieved efficient degradation of difficult-to-degrade organic pollutants in wastewater, with a 10-fold increase in the degradation rate, and the catalyst has good stability and adaptability, and is suitable for complex wastewater conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118491523B_ABST
    Figure CN118491523B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of resource utilization of textile waste and preparation of carbon fiber composite catalyst, and provides a metal-supported carbon fiber catalyst prepared by using textile waste, and its preparation method and application. The textile waste is first activated with H3PO4, impregnated with a metal salt solution, and then dried and calcined at high temperature under an inert atmosphere to obtain a metal-supported carbon fiber catalyst. A metal-supported carbon fiber catalyst is prepared by a one-step calcination method, and is applied to activate persulfate to efficiently degrade refractory organic pollutants in wastewater. The obtained material has a high specific surface area and abundant oxygen-containing functional groups, and the metal active components are uniformly dispersed on the surface of the carbon fiber in the form of C‑O‑R bonds, forming a poor / rich electron center on the catalyst surface. The catalyst can better adapt to the complex conditions of wastewater, and exhibits ultra-high catalytic degradation activity for a variety of pollutants under different anion interferences and different environmental conditions. It has the advantages of low cost, simple process, high processing efficiency, good adaptability, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of resource utilization of textile waste and preparation of carbon fiber composite catalysts, and specifically relates to a metal-loaded carbon fiber catalyst prepared from textile waste, a preparation method and application thereof. A metal-loaded carbon fiber catalyst is prepared from textile waste, and the catalyst is applied to activate persulfate to efficiently degrade refractory organic pollutants in wastewater. Background Art

[0002] China occupies a leading position in the global textile industry, with the total textile fiber processing accounting for more than 50% of the world. However, up to now, the recycling rate of waste textiles is only about 20%, and the rest are mainly treated by incineration and landfill, resulting in huge waste of energy resources and secondary environmental pollution. Therefore, realizing the resource utilization of textile waste is of great significance to saving resources, reducing pollution and reducing carbon emissions.

[0003] Using textile waste as raw materials and preparing carbon fibers by thermal conversion can realize the resource utilization of textile waste. Moreover, the prepared carbon fibers loaded with metal oxides have great application potential in the field of organic pollutant degradation. At present, the research on the preparation of carbon materials from general solid waste mainly focuses on the preparation of traditional powdered biochar or other activated carbon materials using biomass as raw materials. However, such carbon materials usually have poor dispersion of metal oxide nanoparticles embedded on their surfaces or inner walls of pores due to their uneven pore size distribution and irregular morphology, which limits their catalytic degradation efficiency of organic pollutants. In contrast, the preparation of carbon fibers using textile waste with fiber structure as raw materials can obtain regular carbon materials with fiber skeleton structure, and its unique fiber skeleton structure can significantly improve the surface metal dispersion during the metal active component loading process and realize uniform coating of metal oxides. Moreover, compared with powdered activated carbon and granular activated carbon, the unique pore structure and fiber morphology of textile waste ensure that the prepared carbon fibers have more advantages in physical and chemical properties, loading, storage, transportation, etc. Therefore, the preparation of metal-loaded carbon fibers from textile waste has certain theoretical basis and application prospects.

[0004] With the rapid growth of urban scale and industrialization, the types and discharge of environmental sewage are increasing, and the composition is more complex and variable. It contains many difficult-to-degrade organic matter, which poses a great threat to the environment and human health. Refractory organic matter is widely present in printing and dyeing wastewater, chemical wastewater, pharmaceutical wastewater, coking wastewater, etc., and is usually highly toxic, bioaccumulative, and difficult to degrade. The advanced oxidation technology based on persulfate has been widely concerned in degrading difficult-to-degrade organic matter in wastewater due to its fast, efficient, economical, and environmentally friendly characteristics. Metals and their oxides containing multiple valence states, such as Fe 0, Fe3O4, CeO2, CuO, Co3O4, etc. have been proven to have good catalytic effects on the oxidation of refractory organic matter, but the small surface area and poor electron transfer ability of such catalysts limit this catalytic effect to a certain extent. In addition, the catalytic activity is achieved by repeatedly changing the metal valence state through redox reactions at a single active site, which will lead to poor stability of the catalyst, which is also a bottleneck problem currently faced in the catalytic degradation of many organic matter. The preparation of aromatized carbon materials with fiber skeleton structure from low-cost textile waste and the introduction of metal oxides into such solid waste-based carbon fibers are expected to construct poor / rich electron centers on the catalyst surface, which can effectively overcome the above bottleneck problems. In addition, the construction of induced poor / rich electron centers usually depends on the synthesis of inorganic carrier materials, the doping of metal species, and the coordination / complexation of surface carbon structures, and requires a high level of carrier structure, which makes its preparation process complicated and the preparation cost high. The metal-loaded carbon fibers are directly synthesized by a one-step method using textile waste, which is widely available and low-cost, and the process is simple and relatively economical. Therefore, the preparation of metal-loaded carbon fiber catalysts using textile waste and its application in activating persulfate to efficiently degrade difficult-to-degrade organic pollutants in wastewater has guiding significance in specific practice. Summary of the invention

[0005] The first purpose of the present invention is to provide a metal-loaded carbon fiber catalyst prepared using textile waste, aiming to prepare the metal-loaded carbon fiber catalyst using the unique pore structure and fiber morphology of textile waste.

[0006] The second purpose of the present invention is to provide a method for preparing the metal-supported carbon fiber catalyst, and the use of the metal-supported carbon fiber catalyst in activating persulfate to efficiently degrade refractory organic pollutants in wastewater.

[0007] To achieve the above-mentioned purpose, the present invention is implemented by the following technical scheme: a method for preparing a metal-loaded carbon fiber catalyst using textile waste, wherein the textile waste is first activated with H3PO4, impregnated with a metal salt solution, dried, and then calcined at a high temperature in an inert atmosphere, so that the metal active components are evenly dispersed on the surface of the carbon fiber in the form of COR bonds, forming electron-poor / electron-rich centers on the surface of the catalyst, namely, a metal-loaded carbon fiber catalyst.

[0008] Further, the specific steps are as follows:

[0009] (1) Activation of textile waste: Cut the textile waste into pieces of about 3×2 cm, add H3PO4 solution with a mass fraction of 20% to 60%, control the mass volume ratio of textile waste to H3PO4 solution to be between 1g:10 mL and 1g:20 mL, and activate at room temperature for 10-24 h;

[0010] (2) Impregnation with metal salt solution: The activated textile waste is placed in a metal salt solution and immersed in a water bath at 40-60°C for 18-36 hours, and the mass ratio of metal salt to activated textile waste is controlled to be 2wt%-10wt%;

[0011] (3) Calcination: The textile waste impregnated with the metal solution is dried, and then calcined at 500-800°C for 0.5-1.5h at a heating rate of 8°C / min under an inert atmosphere.

[0012] The metal salt solution is any one of a Co(NO3)2 aqueous solution, a Fe(NO3)3 aqueous solution, a Cu(NO3)2 aqueous solution, and a Ce(NO3)3 aqueous solution.

[0013] The inert gas is any one of nitrogen, argon or helium.

[0014] The invention also provides a metal-supported carbon fiber catalyst obtained by the method.

[0015] The present invention also provides the use of the metal-supported carbon fiber catalyst in activating persulfate to degrade refractory organic pollutants in wastewater.

[0016] Further, the specific steps include:

[0017] (1) First, add 0.05-0.25 g / L of metal-supported carbon fiber catalyst to 100 mL of 10-100 mg / L solution of refractory organic pollutants, adjust the pH to 3-11, and then add 0.3-1.1 mmol / L of persulfate. Place the mixed solution in a constant temperature water bath magnetic stirrer at 400 r / s to allow the three to fully mix and react, and start the reaction timer.

[0018] (2) Take 1 mL of the reaction sample within a fixed time period, filter it through a 0.22 μm PES filter head, and add it to a chromatographic bottle containing 0.5 ml of methanol for free radical quenching to terminate the reaction. Determine the concentration of organic pollutants in the sample by liquid chromatography.

[0019] Furthermore, the refractory organic pollutant is any one of bisphenol A (BPA), phenol, tetracycline, rhodamine B, and 2,4-dichlorophenol (2,4-DCP).

[0020] In step (2), 1 mL of the reaction sample is taken within a fixed time period, and the sample is taken at 0, 2, 5, 8, 12, 16, 20, and 30 minutes respectively to perform liquid chromatography to determine the concentration of organic pollutants in the sample.

[0021] The present invention uses textile waste, which is widely available and low in cost, as raw materials, directly performs pre-oxidation carbonization to synthesize carbon fiber materials with orderly structure and controllable performance, and directly synthesizes metal-loaded carbon fibers through a one-step roasting method, thereby realizing the resource application of textile waste. The process is simple, the operation is convenient and relatively economical.

[0022] Powdered biochar or granular activated carbon materials usually have poor dispersion of metal oxide nanoparticles embedded on their surface or pore walls due to their uneven pore size distribution and irregular morphology. Carbon fibers prepared from textile waste with unique fiber morphology can evenly disperse the metals during the loading of metal active components, stably anchor the metal oxides on the carbon fibers through CO-Co bonds, and improve the catalytic degradation efficiency of activated persulfate for difficult-to-degrade organic pollutants.

[0023] The metal-supported carbon fiber prepared by the one-step calcination method has a large specific surface area, rich oxygen-containing functional groups, and a large number of unpaired electrons. A COR bond is formed during the simultaneous calcination process, and a poor / rich electron center reaction mechanism is constructed, which enhances the degradation efficiency of refractory organic matter in wastewater. Compared with the metal-supported catalyst prepared with commercial carbon fiber as the carrier, its degradation rate is increased by 10 times. The catalyst can better adapt to the complex conditions of wastewater, and exhibits ultra-high catalytic degradation activity for a variety of pollutants under different anion interferences and different environmental conditions.

[0024] In summary, the present invention utilizes textile waste to prepare metal-loaded carbon fiber catalysts, which can not only solve the problems of resource waste and environmental pollution, but also effectively solve the problems of resource shortage and high cost of carbon fiber materials in my country, which is in line with my country's green and low-carbon development goals; the metal-loaded carbon fiber material can be used as a cheap, easily available, green, environmentally friendly, efficient and stable catalyst to activate persulfate to efficiently degrade difficult-to-degrade organic pollutants in wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a process flow chart for preparing a metal-supported carbon fiber catalyst using textile waste in Example 1;

[0026] Figure 2 The SEM-EDS images of the metal-supported carbon fiber catalyst prepared in Example 1, wherein: a is a SEM image magnified 1000 times, b is a image magnified 5000 times, c is a image magnified 20000 times, d is an EDS surface scan of the distribution of C elements of the prepared catalyst when magnified 5000 times, e is an EDS surface scan of the distribution of O elements of the prepared catalyst when magnified 5000 times, and f is an EDS surface scan of the distribution of Co elements of the prepared catalyst when magnified 5000 times;

[0027] Figure 3 This is the N2 adsorption-desorption curve of the metal-supported carbon fiber catalyst prepared in Example 1;

[0028] Figure 4 This is the infrared spectrum (FT-IR) of the metal-supported carbon fiber catalyst prepared in Example 1;

[0029] Figure 5 The electron paramagnetic resonance (EPR) image of the metal-supported carbon fiber catalyst prepared in Example 1;

[0030] Figure 6 This is an X-ray photoelectron diffraction (XPS) spectrum of the metal-supported carbon fiber catalyst C1s prepared in Example 1;

[0031] Figure 7 This is the XPS spectrum of the metal-supported carbon fiber catalyst O1s prepared in Example 1;

[0032] Figure 8 This is the XPS energy spectrum of the metal-supported carbon fiber catalyst Co 2p prepared in Example 1.

[0033] Fig. 9 3D fluorescence spectra of the reaction system of Example 9, wherein: a is a 3D fluorescence spectra of BPA, b is a 3D fluorescence spectra of coking wastewater, c is a 3D fluorescence spectra of coking wastewater containing BPA, d is a 3D fluorescence spectra of BPA after 12 min of reaction, e is a 3D fluorescence spectra of coking wastewater after 12 min of reaction, and f is a 3D fluorescence spectra of coking wastewater containing BPA after 12 min of reaction;

[0034] Fig.10 This is the actual chromaticity comparison of the wastewater before and after the reaction in Example 9. In the figure: a is the chromaticity comparison of coking wastewater before and after treatment, and b is the chromaticity comparison of coking wastewater containing BPA before and after reaction. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0036] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs, and the disclosure and materials cited therein are hereby incorporated by reference.

[0037] Technical equivalents to the specific embodiments described that are apparent to those skilled in the art using no more than routine experimentation are intended to be encompassed by this application.

[0038] The experimental methods in the following examples are all conventional methods unless otherwise specified. The instruments and equipment used in the following examples are all conventional laboratory instruments and equipment unless otherwise specified; the experimental materials used in the following examples are all purchased from conventional biochemical reagent stores unless otherwise specified.

[0039] Example 1: A method for preparing a metal-supported carbon fiber catalyst using textile waste, the preparation process is as follows Figure 1 As shown, specifically:

[0040] (1) Activation: Cut the cotton cloth into pieces of approximately 3 × 2 cm, weigh 3 g and immerse it in 50 mL 40 wt% H3PO4 for 12 h;

[0041] (2) Impregnation: The activated cotton cloth was placed in a solution of 0.55 g Co(NO3)2·6H2O dissolved in 10 mL ultrapure water, and then immersed in a 40°C water bath for 24 h.

[0042] (3) Calcination: The above samples were placed in an oven at 80 °C for 10 h for drying; the products were transferred to a porcelain boat and calcined in a tubular furnace at 600 °C for 1 h in a nitrogen (N2) atmosphere to obtain the catalyst Co3O4@ACF.

[0043] The SEM-EDS image of the obtained metal-supported carbon fiber catalyst is as follows: Figure 2 As shown, the N2 adsorption-desorption curve is as follows Figure 3 As shown, the infrared spectrum (FT-IR) is as follows Figure 4 As shown in the above figure, the metal-supported carbon fiber catalyst prepared by using textile waste in the present invention has a unique fiber morphology ( Figure 2 ) and pore size distribution ( Figure 3 ), larger specific surface area ( Figure 3 ) and abundant oxygen-containing functional groups ( Figure 4 ).

[0044] The microstructure of Co3O4@ACF can be observed through SEM images. Figure 2 a shows that Co3O4@ACF presents a fiber structure, which verifies the feasibility of preparing carbon fiber catalysts from textile waste. Figure 2 c It can be seen that the surface of ACF is uniformly inlaid with small particles of Co3O4, indicating that Co3O4@ACF prepared by a one-step calcination method can achieve uniform coating of Co3O4 on ACF.

[0045] The specific surface area and pore size analysis of Co3O4@ACF were studied by N2 adsorption-desorption experiments. Figure 3 As shown in Figure 2, the adsorption-desorption isotherm can be described as a type I isotherm with a type IV hysteresis loop, which indicates that Co3O4@ACF has micro-mesoporous properties. The specific surface area of ​​Co3O4@ACF reaches 412.1 m 2 / g, the average pore size increases, which can provide more active sites for catalytic degradation of organic matter.

[0046] The surface functional groups of Co3O4@ACF were studied by FTIR, such as Figure 4 As shown. At 3436 cm -1 、2923 cm -1 , 2852 cm -1 、1736 cm -1 、1629 cm -1 , 1045 cm -1 The observed characteristic bands can be attributed to -OH, -CH3, -CH2, C=O, C=C and CO groups, among which C=O is a basic oxygen-containing functional group. 1 O2 plays a key role in the generation of CO, and CO is an important basis for inducing the formation of electron-poor / electron-rich centers in CO-Co, which is one of the reasons why Co3O4@ACF has excellent catalytic performance. -1 、561 cm -1 The characteristic spectral bands attributed to Co3O4 further prove that Co is loaded on ACF in the form of Co3O4.

[0047] Metal-loaded carbon fibers were prepared by a one-step calcination method using textile waste as raw materials. Metal ions can participate in the carbonization of cellulose during the calcination process and enter the structure of the carbon fibers, thereby changing the electron distribution of the catalyst. In order to verify the electron transfer efficiency of the textile waste-based carbon fiber ACF catalyst, solid EPR tests were carried out, such as Figure 5 As shown. It is worth noting that a high-intensity unpaired electron signal was detected on Co3O4@ACF. The formation of a large number of unpaired electrons gives Co3O4@ACF a higher catalytic performance in the process of activating PMS to degrade BPA.

[0048] The surface element composition and surface metal valence state of Co3O4@ACF were studied by XPS. Figure 6-8 shown. Figure 6In the C 1s fine spectrum of Co3O4@ACF, the peaks at 284.80, 286.15 and 289.07 ev can be attributed to CC / C=C, CO and C=O. Among them, the presence of CC / C=C bonds indicates that Co3O4@ACF forms an aromatic C (π) structure, while the higher binding energy of the CO characteristic peak in the C 1sXPS spectrum of Co3O4@ACF indicates that Co3O4@ACF forms a CO-Co bond bridge structure. In the O 1s fine spectrum of Co3O4@ACF ( Figure 7 ), the peaks at 530.33 and 532.34 can be attributed to the characteristic peaks of lattice oxygen and surface oxygen of Co3O4@ACF, while the peak at 531.45 ev located between lattice oxygen and surface oxygen can be attributed to the characteristic peak of CO-Co bond, which is consistent with the XPS spectrum of C 1s. Figure 8 ), the peaks at 781.56 and 797.84 ev can be attributed to Co2p3 / 2 and Co 2p1 / 2, and the peaks at 786.22 and 803.25 ev can be attributed to the satellite peaks of Co. The Co2p3 / 2 peak at 781.56 ev can be further divided into Co 2+ The characteristic peak of 783.09 eV and Co 3+ The characteristic peak of 781.60 ev was obtained by Gaussian fitting. 2+ and Co 3+ The ratio is 1.99.

[0049] In summary, the metal-supported carbon fiber catalyst prepared from textile waste in the present invention has a large specific surface area and abundant oxygen-containing functional groups, and a large number of unpaired electrons are distributed around the CO-Co bond. These characteristics are helpful for the metal-supported carbon fiber catalyst to activate persulfate to efficiently degrade bisphenol A (BPA).

[0050] Example 1: Application of metal-supported carbon fiber catalyst Co3O4@ACF prepared from textile waste to activate PMS and degrade BPA, the specific steps are as follows:

[0051] (1) Add 100 mL of 50 mg / L BPA solution to a 250 mL beaker, add 0.15 g / L metal-supported carbon fiber catalyst, adjust the pH to 3-11, and then add 0.7 mmol / L persulfate. After mixing the above solutions, place them in a constant temperature water bath with a magnetic stirrer at 400 r / s and start the reaction timing.

[0052] (2) 1 mL of sample was taken with a disposable syringe at 0, 2, 5, 8, 12, 16, 20, and 30 min, respectively. The sample was filtered through a 0.22 μm PES filter and added to a 2 mL chromatographic vial. 0.5 mL of methanol was added to the chromatographic vial in advance to quench the free radicals and terminate the reaction. The concentration of BPA in the sample was determined by liquid chromatography.

[0053] (3) After the degradation experiment was completed, the solution was filtered to obtain the catalyst after the reaction, which was placed in 100 mL of ethanol and ultrasonically dispersed for 45 minutes. The effect of adsorption on the degradation removal rate of bisphenol A was eliminated, and the concentration of bisphenol A in the solution was determined by liquid chromatography to obtain the concentration of bisphenol A adsorbed by the catalyst. Thus, the concentration of bisphenol A degraded by the catalyst can be known. The results showed that the high concentration of 50 mg / L BPA was completely degraded within 12 minutes.

[0054] Comparative Example 1: Preparation of Co3O4@ACF using commercial carbon fiber CF as carrier to activate persulfate to degrade bisphenol A (BPA). Except that the cotton cloth in Example 1 was replaced with commercial carbon fiber, the other steps and conditions were the same as those in Example 1. The results are shown in Table 1. It can be found that the system Co3O4@CF / PMS using commercial carbon fiber CF as carrier can achieve complete degradation of BPA in 120 min, and its degradation time is 10 times that of the Co3O4@ACF / PMS system.

[0055] Among them, the Co3O4@CF prepared with commercial carbon fiber CF as the carrier in Comparative Example 1 is prepared by the following steps:

[0056] (1) Weigh 3 g of commercial carbon fiber CF and soak it in 40 wt% H3PO4 for 12 h;

[0057] (2) The activated commercial carbon fibers were placed in a solution of 0.55 g Co(NO3)2·6H2O dissolved in 10 mL ultrapure water and then immersed in a 40 °C water bath for 24 h.

[0058] (3) The above sample was placed in an oven at 80 °C for 10 h for drying; the product was transferred to a quartz ark and calcined at 600 °C for 1 h in a tube furnace under a nitrogen (N2) atmosphere to obtain the catalyst Co3O4@CF.

[0059] Table 1: Comparison of catalytic performance between the PMS system of Co3O4@ACF and the PMS system of Co3O4 / CF

[0060]

[0061] Example 2: The effect of different catalyst dosages on the removal rate of bisphenol A (BPA) in wastewater was investigated. Except for the different catalyst dosages, the other steps and methods were the same as in Example 1, wherein the preparation of the metal-supported carbon fiber catalyst was consistent with the preparation method in Example 1. The results are shown in Table 2. When the dosage was increased to 0.25 g / L, the complete degradation of BPA could be achieved within 8 min. This once again proves the high catalytic ability of Co3O4@ACF. It shows that as the dosage of Co3O4@ACF increases, the active sites in the system increase, and the efficiency of activating PMS increases.

[0062] Table 2: Effect of different catalyst Co3O4@ACF dosage on the removal rate of bisphenol A in wastewater

[0063]

[0064] Example 3: The effect of different PMS dosages on the removal rate of bisphenol A in wastewater was investigated. Except for the different PMS dosages, the other steps and methods were the same as those in Example 1, wherein the preparation of the metal-supported carbon fiber catalyst was consistent with the preparation method in Example 1. The results are shown in Table 3. Even when the PMS dosage was 0.30 mM / L, the degradation rate of BPA within 30 min could reach 96%, indicating that the catalyst had a high activation ability for PMS. Moreover, when the dosage was increased to 1.10 mM / L, complete degradation of BPA was achieved within 8 min.

[0065] Table 3: Effect of different PMS dosage on the removal rate of bisphenol A in wastewater

[0066]

[0067] Example 4: The effects of different initial bisphenol A (BPA) concentrations were investigated in the Co3O4@ACF system. Except for the different initial bisphenol A concentrations, the other steps and methods were the same as those in Example 1, and the preparation of the metal-supported carbon fiber catalyst was consistent with the preparation method in Example 1. The results are shown in Table 4. 10 mg / L BPA was completely degraded within 5 min, and even high concentrations of 75 mg / L and 100 mg / L BPA achieved 95% and 90% degradation rates within 30 min.

[0068] Table 4: Effect of different initial bisphenol A (BPA) concentrations on the removal rate of bisphenol A in wastewater

[0069]

[0070] Example 5: The effect of different initial pH in the water body on the removal rate of bisphenol A (BPA) in wastewater was investigated. Except for the different initial pH in the water body, the other steps and methods were the same as in Example 1, wherein the preparation of the metal-supported carbon fiber catalyst was consistent with the preparation method in Example 1. As shown in Table 5, the performance of Co3O4@ACF activated PMS to degrade BPA was less affected by pH, and BPA could be completely degraded within 20 min at pH 3.07, 4.23, 6.6, 8.78, and 11.07. This shows that Co3O4@ACF has a wide pH range of application. This is mainly because there are a large number of CO-Co bonds in the prepared catalyst structure, which further induces the formation of poor-rich electron centers and enhances the environmental tolerance of Co3O4@ACF.

[0071] Table 5: Effect of different initial pH on the removal rate of bisphenol A in wastewater

[0072]

[0073] Example 6: The degradation performance of Co3O4@ACF on BPA under different anion interferences was investigated. In addition to adding 10 mM / L CO3 2- 、HCO3 - , Cl - 、SO4 2- Except for the coexisting anion, the other steps and methods are the same as those in Example 1, wherein the preparation method of the metal-supported carbon fiber catalyst is the same as that in Example 1. The results are shown in Table 6. 10 mM / L SO4 - and Cl - When 10 mM / L CO3 was added, the system was promoted and the complete degradation of BPA was achieved within 8 min. 2- and HCO3 - When the degradation of BPA was slightly inhibited, the degradation rate could still be maintained above 90% at 30 min (degradation rates were 90% and 94%). This again shows that the Co3O4@ACF / PMS system is less affected by the coexisting anions, indicating that Co3O4@ACF has strong environmental adaptability.

[0074] Table 6: Effect of different anions on the removal rate of bisphenol A in wastewater

[0075]

[0076] Example 7: The degradation performance of Co3O4@ACF on different organic pollutants was investigated. Except for the different organic matter to be degraded, the other steps and methods were the same as those in Example 1, wherein the preparation of Co3O4@ACF was consistent with the preparation method in Example 1. The results are shown in Table 7. The Co3O4@ACF / PMS system has good degradation performance for phenol, 2,4-DCP, tetracycline and rhodamine B. Except for phenol, all of them were completely degraded within 16 minutes, especially rhodamine B, which was completely degraded within 5 minutes. Even phenol, which had the worst degradation effect, was degraded by 90% within 30 minutes, indicating that Co3O4@ACF has good universality and high catalytic ability.

[0077] Table 7: Degradation performance of Co3O4@ACF on different organic pollutants

[0078]

[0079] Example 8: The catalytic performance of Co3O4@ACF in treating actual coking wastewater was investigated. The changes in the coking wastewater during the purification process were analyzed by three-dimensional fluorescence spectroscopy. The results are as follows: Fig. 9 As shown. The preparation of Co3O4@ACF is consistent with the preparation method in Example 1. After the Co3O4@ACF / PMS system reacted in three aqueous solutions of 50 mg / LBPA, coking wastewater, and coking wastewater containing 50 mg / LBPA solution for 12 min, the peak corresponding to BPA in the water was completely removed, and the fluorescence intensity corresponding to other substances decreased significantly, indicating that the system can effectively purify coking wastewater. Fig.10 The chromaticity changes of coking wastewater and coking wastewater containing BPA before and after reaction for 12 minutes. It can be seen that the chromaticity of coking wastewater decreases with the degradation of pollutants, which further proves that the system also has good purification ability for actual wastewater.

[0080] Example 9: A method for preparing a metal-loaded carbon fiber catalyst using textile waste. The textile waste is cut into pieces of 3×2 cm, a 20% by mass H3PO4 solution is added, and the pieces are left to stand for activation at room temperature for 10 hours; the activated textile waste is placed in a metal salt solution with a concentration of 0.01 g / ml and immersed in a 50°C water bath for 18 hours; the textile waste immersed in the metal solution is dried, and then calcined at a controlled temperature of 500°C in an inert atmosphere. The remaining methods are the same as those described in Example 1.

[0081] Example 10: A method for preparing a metal-loaded carbon fiber catalyst using textile waste, wherein the textile waste is cut into pieces of 3×2 cm, a 60% by mass H3PO4 solution is added, and the pieces are left to stand for activation at room temperature for 24 hours; the activated textile waste is placed in a metal salt solution with a concentration of 0.1 g / ml and immersed in a 60°C water bath for 36 hours; the textile waste immersed in the metal solution is dried, and then calcined at a controlled temperature of 800°C in an inert atmosphere, and the remaining methods are the same as those described in Example 1.

[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a metal-supported carbon fiber catalyst using textile waste, characterized in that: The textile waste is first activated with H3PO4, impregnated with a metal salt solution, dried, and then calcined at high temperature in an inert atmosphere, so that the metal active components are evenly dispersed on the carbon fiber surface in the form of COR bonds, forming poor / rich electron centers on the catalyst surface, that is, metal-supported carbon fiber catalysts; The specific steps are as follows: (1) Activation of textile waste: Cut the textile waste into pieces of 3×2 cm, add H3PO4 solution with a mass fraction of 20%~60%, control the mass volume ratio of textile waste to H3PO4 solution to be between 1g:10 mL-1g:20 mL, and activate at room temperature for 10-24h; (2) Impregnation with metal salt solution: Place the activated textile waste in the metal salt solution, immerse it in a water bath at 40-60℃ for 18-36h, and control the mass ratio of metal salt to activated textile waste to be 2wt%-10wt%; (3) Calcination: Dry the textile waste after impregnation with the metal solution, and then heat it to 500-800℃ in an inert atmosphere at a heating rate of 8℃ / min and calcine it for 0.5-1.5h.

2. The method according to claim 1, characterized in that: The metal salt solution is any one of a Co(NO3)2 aqueous solution, a Fe(NO3)3 aqueous solution, a Cu(NO3)2 aqueous solution, and a Ce(NO3)3 aqueous solution.

3. The method according to claim 1, characterized in that: The inert atmosphere is any one of nitrogen, argon or helium.

4. A metal-supported carbon fiber catalyst obtained by the method according to any one of claims 1 to 3.

5. Use of the metal-supported carbon fiber catalyst according to claim 4 in activating persulfate to degrade refractory organic pollutants in wastewater.

6. The use according to claim 5, characterized in that: The specific steps include: (1) First, add 0.05-0.25 g / L of metal-supported carbon fiber catalyst to 100 mL of 10-100 mg / L solution of refractory organic pollutants, adjust the pH to 3-11, then add 0.3-1.1 mmol / L of persulfate, place the mixture in a constant temperature water bath magnetic stirrer at 400 r / s to allow the three to fully mix and react, and start the reaction timing; (2) Take 1 mL of the reaction sample within a fixed time period, filter it through a 0.22 μm PES filter head, and add it to a chromatographic bottle containing 0.5 ml of methanol for free radical quenching to terminate the reaction. Determine the concentration of organic pollutants in the sample by liquid chromatography.

7. The use according to claim 6, characterized in that: The refractory organic pollutant is any one of bisphenol A (BPA), phenol, tetracycline, rhodamine B, and 2,4-dichlorophenol (2,4-DCP).

8. The use according to claim 6, characterized in that: In step (2), 1 mL of the reaction sample is taken within a fixed time period, and the sample is taken at 0, 2, 5, 8, 12, 16, 20, and 30 minutes respectively to perform liquid chromatography to determine the concentration of organic pollutants in the sample.

Citation Information

Patent Citations

  • Cotton carbon fiber monolithic catalyst as well as preparation method and application thereof

    CN113117660A